2012
DOI: 10.1097/phm.0b013e318269eceb
|View full text |Cite
|
Sign up to set email alerts
|

How Assistive Technology Use by Individuals with Disabilities Impacts Their Caregivers

Abstract: Informal caregivers are a critical, yet frequently unacknowledged part of the healthcare system. It is commonly presumed that providing assistive technology (AT) will decrease the burden of their care provision; however, no review has evaluated the evidence behind this assumption. Therefore, a systematic reviews was undertaken to evaluate evidence of the impact of AT use by care-recipients on their informal caregivers. Data Sources included Embase, Medline, Cumulative Index to Nursing and Allied Health Literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 51 publications
(146 reference statements)
5
61
2
1
Order By: Relevance
“…The results from this study confirm previous studies showing that spouses are profoundly influenced by the introduction of an ATD [31] and that the use of an ATD can benefit caregivers by decreasing their required efforts [32,33]. In addition to expanding participation for older individuals in their diverse contexts, the introduction of an ATD can also provide other people with new abilities with which to address their difficulties.…”
Section: Discussionsupporting
confidence: 79%
“…The results from this study confirm previous studies showing that spouses are profoundly influenced by the introduction of an ATD [31] and that the use of an ATD can benefit caregivers by decreasing their required efforts [32,33]. In addition to expanding participation for older individuals in their diverse contexts, the introduction of an ATD can also provide other people with new abilities with which to address their difficulties.…”
Section: Discussionsupporting
confidence: 79%
“…Also, Mortenson et al (2012) carry out a systematic review of the literature on the topic that suggests that assistive technologies is associated with relief to caregivers in terms physical and emotional effort.…”
Section: What Constitutes Ltc?mentioning
confidence: 99%
“…In addition, children with physical disabilities mentioned that assistive technology increased their self-confidence and productivity (Carpe et al 2010), and disabled people who used assistive technology in school were more likely to participate in post-secondary education (Bouck, Maeda, and Flanagan 2012). Moreover, literature reviews identified that assistive technology reduces some of the physical and emotional effort entailed in supporting disabled individuals (Ben Mortenson et al 2012) and that modern technology has the potential to increase independence and to decrease the costs of efficient care (Sestic et al 2012). …”
Section: Effects Of Self-help Support Groups and Assistive Technologymentioning
confidence: 99%